Magnetic and Electrical Transport Properties of Double Perovskite Sr2FeMoO6 Prepared by Sol-Gel Method - Yong-Qing Zhai; Jing Qiao; Zhang Zhang (E-Journal of Chemistry)
With activated carbon for reducing agent, the sol-gel method was used to prepare the giant magnetoresistance materials Sr2FeMoO6, which is the double Perovskite oxide. The structure, morphology, magnetic and electrical transport properties were investigated respectively by x-ray diffraction, scanning electron microscopy and vibrating sample magnetometer. The as-synthesized sample is Sr2FeMoO6 with tetragonal crystal structure and I4/mmm space group and unit cell parameter is a = 5.580Å, c = 7.882Å. The primary particles are spherical in shape and the grain size is below 100 nm. The curie temperature is above room temperature and the saturation magnetization is 13.321 A·m2/kg under 1.0 T at room temperature. The sample exhibit typical semiconductor behavior and the conductive mechanism can be described by small polaron variable range hopping model. The room temperature magnetoresistance of the sample under 1.0 T field is up to -10.02%. Moreover, it is found the dosage of citric acid and the amount of reducing agent has great effect on the phase structure and magnetic properties of the samples.